Microstructural and optical characterization of CaWO4 and SrWO4 thin films prepared by a chemical solution method - Maurera, MAMA; Souza, A. G.; Soledade, LEB; Pontes, F. M.; Longo, Elson [UNESP]; Leite, E. R.; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
Stoichiometric CaWO4 and SrWO4 thin films were synthesized using a chemical solution processing, the so-called polymeric precursor method. In this soft chemical method, soluble precursors such as strontium carbonate, calcium carbonate and tungstic acid, as starting materials, were mixed in an aqueous solution. The thin films were deposited on glass substrates by means of the spinning technique. The surface morphology and crystal structure of the thin films were investigated using X-ray diffraction (XRD), scanning electron microscopy (SEM), and atomic force microscopy (AFM). Nucleation stages and surface morphology evolution of the thin films on glass substrates were studied by atomic force microscopy. The films nucleate at 300 degreesC, after the coalescence of small nuclei into larger grains yielding a homogeneous dense surface. XRD characterization of these films showed that the CaWO4 and SrWO4 phases crystallize at 400 degreesC from an inorganic amorphous phase. No intermediate crystalline phase was identified. The optical properties were also studied. It was found that CaWO4 and SrWO4 thin films have an optical band gap, E-gap=5.27 and 5.78 eV, respectively, of a direct transition nature. The excellent microstructural quality and chemical homogeneity confirmed that this soft solution processing provides an inexpensive and environmentally friendly route for the preparation of CaWO4 and SrWO4 thin films. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: CaWO4; SrWO4; scheelite-type structure; chemical solution method; thin films